Mediterranean Diet: From a Healthy Diet to a Sustainable Dietary Pattern - Dernini, Sandro; Berry, Elliot M. (Frontiers in Nutrition, 2015)
The notion of the Mediterranean Diet has undergone a progressive evolution over the past 60 years, from a healthy dietary pattern to a sustainable dietary pattern, in which nutrition, food, cultures, people, environment and sustainability all interact into a new model of a sustainable diet. An overview of the historical antecedents and recent increased interest in the Mediterranean diet is presented and challenges related how to improve the sustainability of the Mediterranean diet are identified. Despite its increasing popularity worldwide, adherence to the Mediterranean diet model is decreasing for multifactorial influences – life styles changes, food globalization, economic and socio-cultural factors. These changes pose serious threats to the preservation and transmission of the Mediterranean diet heritage to present and future generations. Today’s challenge is to reverse such trends. A greater focus on the Mediterranean diet's potential as a sustainable dietary pattern, instead than just on its well documented healthy benefits, can contribute to its enhancement. More cross-disciplinary studies on environmental, economic and socio-cultural, sustainability dimensions of the Mediterranean diet are foreseen as a critical need.